The resurgence of religion : a comparative study of selected themes in Christian and Islamic fundamentalist discourses - Zeidan, David (Studies in the history of religions, 2003)
A comparative study of basic themes in Christian and Islamic fundamentalist discourses, analyzing texts from a wide variety of leaders and movements. It looks for "family resemblances" and significant differences in order to better understand the contemporary phenomenon of religious resurgence.